Penerapan Sistem Informasi Manajemen Kredit dan Akuntansi Pada Unit Usaha Kredit BUMDes Catur Eka Amertha - I Made Dwi Putra Asana; Ni M.M.R. Desmayani; K. Jaya Atmaja; I N.T.A. Putra; A.A.G.Bagus Ariana (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2022)
BUMDes Catur Eka Amertha is a business entity owned by Angantaka Village, Abiansemal District, Badung Regency. BUMDes Catur Eka Amertha is the target partner of the team proposing Community Service activities. Partners have problems in the field of credit data management and accounting. Credit data management is important to ensure nominal income generated by credit units. The management system that has been carried out so far has implemented several processes from paper, excel work paper files, and accounting report files. The obstacle experienced is that the resulting information cannot be accessed directly. The constraints on access to information have an impact on the development of business development strategies. The Community Service activities proposer team applies science and technology as a solution to solving problems for partners. In the field of data management, the proposing team designed and built computer-based credit management and accounting information system. Partners are then given training in operating the management information system that has been built. The system has been implemented in the operational process of the credit business unit and has produced credit and accounting reports for BUMDes Catur Eka Amertha. The outputs of Community Service activities are increasing the application of science and technology in the community, the scientific publication of the results of Community Service activities in ISSN journals, and the publication of the results of activities in print or online mass media.